Strategy for Management of Assistance Management Information System (SIMBA PD Pontren) Through EMIS Integration to Improve Public Service Quality at The Ministry of Religious Affairs of The Republic Indonesia - Ahmad Kamal Assidiqi; Hidayah, Siti Nur (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2026)
Data and information are vital in supporting policies and resource management, especially within the Islamic education sector. The Ministry of Religious Affairs (Kemenag), through Ministerial Decree (KMA) Number 83 of 2022, aims to integrate Islamic education data into an organized system, particularly through the Education Management Information System (EMIS). Despite EMIS being the primary platform for data management, challenges persist in integrating it with other systems such as SIMBA PD Pontren. Issues such as data discrepancies between EMIS and SIMBA PD Pontren, along with infrastructure limitations, affect the accuracy of educational assistance distribution for pesantren. This study aims to analyze governance strategies that optimize the integration of EMIS and SIMBA PD Pontren to improve the efficiency and quality of Islamic education data management. Using a qualitative approach with a case study method, the research was conducted at the Directorate of Diniyah Education and Pesantren from October 14 to November 8, 2024. The study involved six participants directly engaged in the implementation of SIMBA PD Pontren. Data were collected through observation, in-depth interviews, and document review, with analysis following an interactive approach to ensure credibility, dependability, and confirmability. The findings indicate that EMIS integration is crucial for ensuring data validity and supporting policy-making in Islamic education. Key governance strategies include clear operational regulations, strict data verification, and stakeholder participation, which have enhanced public service quality, particularly through the Telepontren application.